2002
DOI: 10.1046/j.1365-2044.2002.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and coronary heart disease

Abstract: SummaryEarly studies indicated that isoflurane caused coronary steal and should therefore be avoided in patients with coronary heart disease. Subsequently, more detailed trials have disputed this and have shown that as long as coronary perfusion pressure is maintained, isoflurane does not cause coronary steal or myocardial ischaemia. There is now growing evidence, initially in animal work but more recently in human studies, that isoflurane has myocardial protective properties, limiting infarct size and improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 69 publications
(64 reference statements)
0
9
1
Order By: Relevance
“…Moreover, although isoflurane was initially thought to cause coronary steal, subsequent studies showed that isoflurane is probably beneficial to patients with coronary heart disease by reducing myocardial stunning and infarct size (Agnew et al, 2002). On the other hands, isoflurane has also been reported to be hepatotoxic, cytotoxic and genotoxic compounds in humans (Kenna and Jones, 1972;Kvolik et al, 2005;Anders, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, although isoflurane was initially thought to cause coronary steal, subsequent studies showed that isoflurane is probably beneficial to patients with coronary heart disease by reducing myocardial stunning and infarct size (Agnew et al, 2002). On the other hands, isoflurane has also been reported to be hepatotoxic, cytotoxic and genotoxic compounds in humans (Kenna and Jones, 1972;Kvolik et al, 2005;Anders, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon describes a redistribution of collateral blood flow away from ischaemic regions, thus suggesting that isofluarne would exacerbate the ischaemic insult in an already compromised myocardial region. Although isoflurane has been shown to cause coronary steal in experimental models of chronic coronary occlusion (for example, Buffington et al , 1987 ), most clinical studies did not (reviewed in Agnew et al , 2002 ). Key factors responsible for this controversy have been poor control of haemodynamics and lack of evidence supporting steal‐prone anatomy.…”
Section: Anaesthetics As Cardioprotective Agentsmentioning
confidence: 99%
“…Whether isoflurane causes coronary steal is controversial, but its use in patients with angina is considered safe (8,9). Intraoperatively, our patient had isoflurane as low as 0.1% end-tidal without improvement of the ST segment.…”
Section: Discussionmentioning
confidence: 94%